DEVELOPMENT OF MATHEMATICS LEARNING INTERACTIVE MEDIA THROUGH REALISTICS MATHEMATIC EDUCATION APPROACH USING ARTICULATE STORYLINE 3 TO IMPROVE MATHEMATICS PROBLEM SOLVING ABILITY FOR SMA NEGERI 14 MEDAN - Andri Samuel Siagian; Dian Armanto (International Journal Labs, 2022)
This research was conducted with the aim of producing interactive learning media using Articulate Storyline 3 through the Realistics Mathematical Education approach that is valid, practical, effective and able to improve students' mathematical problem solving skills on the material of a two-variable linear equation system. This study uses a Research and Development (R & D) type of research with the development model used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were students of class X MIPA 2 SMA Negeri 14 Medan with a total of 32 people. Based on the research that has been done, the results of the validation of material experts with a percentage of 94% are in the very valid category, while the results of media expert validation are obtained with a percentage of 96% in the very valid category. The practicality of learning media is seen through the results of student and mathematics teacher and student response questionnaires with a percentage of 90% and 95% where these percentages are in the very practical category. The effectiveness of learning media is seen through classical learning completeness and the results of student response questionnaires with a percentage of 87.5% and 90% where these percentages are in the very effective category. Improved problem solving skills in students, the results obtained by the level of problem solving abilities of students are in the percentage of 78% in the high category, while based on the N-Gain test the average value obtained by students is 0.483 which means that there is an increase in problem solving abilities in students. with medium category. So based on the results obtained, it can be concluded that the learning media developed in this study is valid, practical, effective and able to improve students' mathematical problem solving abilities.